Wie prekär ist Zeitarbeit? Eine Analyse mit dem Matching-Ansatz - Matthias Dütsch (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– In recent years temporary agency employment has become a very dynamically growing form of employment in the German labour market. Due to the current development, many scientific papers have been published. However, it is not possible to combine previous quantitative research into several aspects of working conditions in temporary agency employment to a consistent picture. This article presents a comprehensive analysis on working conditions of temporary agency workers. By using the German Socio-Economic Panel Study (GSOEP) the question will be answered, how precarious temporary agency employment really is. For this purpose seven dimensions will be defined and operationalised with subjective and objective items from the surveys in the years 2006 and 2007. A Propensity Score Matching approach will be deployed to form a valid control group for the temporary agency workers. The evaluation of working conditions in temporary agency employment is a two-stage procedure. First, the results of the empirical analysis will be assessed from a comparative analytical perspective. This is to investigate whether temporary workers are disadvantaged in comparison to control subjects. Then, the question of whether temporary agency employment is precarious will be addressed by testing by means of objective criteria. The findings show that temporary agency workers are disadvantaged in a specific way. This applies to wages, employment stability and health related risks involved, as well as to work satisfaction. Furthermore, temporary agency employment is precarious due to employment instability. Feasible disadvantages in regard to opportunities for qualification and recognition are however attributable to job specific as well as individual characteristics. Thus, temporary agency employment cannot be identified as precarious concerning most of the analyzed dimensions.
Keywords: 330; atypische Beschäftigung; Zeitarbeit; Arbeitsbedingungen; Prekariat; Zeitarbeitnehmer; Benachteiligung; Lohndiskriminierung; Arbeitszufriedenheit; Weiterbildungsangebot; Leiharbeit; Leiharbeitnehmer; Randbelegschaft; Arbeitnehmerüberlassung; Beschäftigungsdauer; Arbeitsbelastung; Gesundheitszustand